PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PT. INTI INDOSAWIT SUBUR KECAMATAN MARO SEBO ILIR DI KABUPATEN BATANGHARI - Etty Siswati (Universitas Batanghari Jambi, 2015)
The purpose of this study were (1) .To determine the influence of leadership style on employee performance of PT Inti Subur Indosawit Maro Sebo Ilir in Batanghari regency. (2) .To determine the influence of the work environment on employee performance PT.Inti Indosawit Fertile Maro Sebo Ilir in Batanghari regency. (3) .To determine the effect of leadership style and work environment to employees performance at PT.Inti Indosawit Fertile Maro Sebo Ilir in the district of Batanghari.Methods of data collection used a survey method was used to obtain information from respondents by using interview techniques and distribute a list of questions and by using a Likert scale measurement. The population in this study is covering all employees at PT. Subur Indosawit core Maro Sebo Ilir Batanghari regency. The number of 57 employees. Data analysis tool used is multiple regression method uses computer assistance through the program SPSS 20.0 for windows.Leadership Style analysis results showed positive and significant impact on the performance of employees at PT.Inti Indosawit Subur in Batanghari regency. Work Environment and significant positive effect on employee performance PT.Inti Indosawit Fertile Maro Sebo Ilir in Batanghari regency.Keywords: leadership style, work environment, employee performance, PT.Inti Indosawit Subur Maro Sebo Ilir Batanghari district.